Perancangan Interior Resto Edukasi Masakan China di Surabaya - Utama, Elisabeth Kristina (Intra, 2013)
Restaurant is one alternative place that aims to meet the primary needs of human beings which is eating. Nowadays, eating is no longer just a necessity but also as a hobby so that the term